Damping heat coefficient – Theoretical and experimental research on a vibrating beam. (21st July 2017) - Mihalec, Marko; Javh, Jaka; Cianetti, Filippo; Moretti, Michele; Rossi, Gianluca; Slavič, Janko; Boltežar, Miha
Abstract: Vibrating systems dissipate their vibrational energy through different mechanisms, commonly referred to as damping. Damping converts the vibrational energy into other forms, such as heat and sound radiation. Heating of the material is often assumed to be one of the biggest drains of energy; however, the measurable temperature increase is at the level of milli Kelvin and hard to measure. This research introduces a damping heat coefficient, the coefficient of total dissipated energy that is converted into heat. Using this coefficient, the expected temperature change of a beam is theoretically related to its damping ratio. In addition, the damping heat coefficient is determined experimentally by measuring the temperature increase of a vibrating beam. Based on modal damping, it is shown that different amounts of energy are dissipated at different parts of the structure. The numerical heat model was experimentally confirmed. Abstract : Highlights: Experimental identification of the damping energy that is dissipated to heat. The experimental identification bases on the milli Kelvin changes of the surface temperature. The damping heat coefficient defines the damping energy that is dissipated to heat. For the polymethyl methacrylate material, the damping heat coefficient was found to be approximately 30%.